A Construction Technique of Incremental Launching for a Continuous Steel Truss Girder Bridge with Suspension Cable Stiffening Chords. Issue 1 (2nd January 2021) - Shi-hong, Ding; Ji, Fang; Shi-li, Zhang; Chong-shuang, Liang
Abstract: Ji'nan Huanghe rail-cum-road bridge is a continuous steel truss girder bridge with rigid suspension stiffening chords. Considering the structural characteristics and construction conditions of the huge steel truss girder, a technique of incremental launching method with suspension cable stiffening chords was used for construction of the bridge. For the design of the support structures, assembling supports were used at the side spans and pier-side brackets were used at the central spans. During construction of the horizontal launchings, vertical jack-ups and transverse offsetting rectifying devices were arranged. The functions of the incremental launching devices and support system were qualified to realize the complicated construction work. An advanced synchronous control system was applied to implement the multi-point synchronous incremental launching. The strategy of using elastic support pads was proposed to decrease the harmful influences of the height differences of the three main trusses during construction. Using the finite element analysis, the controlling values of the height differences were determined between +15 and -25 mm to ensure the safety of the construction. The technique given in this paper could provide a reference for the construction of similar long-span bridges.